Pickford Ford at an old inn - Pickford, Joel:::::::::
Pickford Ford at an old inn on the Ghost Road, taken while on a story assignment for Ford Times Magazine. Ford regularly published the watercolors it commissioned in both Ford Times and Lincoln-Mercury Times magazines